Investigation of stabilization of a mathematical model of a dynamical system with random influence in the resonance case - Dzhalladova, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We construct and investigate a mathematical model of a dynamical system with random influence stabilized by increasing the frequency of random influence.